The Correlation Between Age and Body Mass Index and The Incidence of Osteoarthritis in The Elderly at Outpatient Unit of PKU Muhammadiyah Sekapuk Hospital - Nofita Syafaatin; Diah Jerita Eka Sari; Ervi Suminar; Widiharti Widiharti (Universitas Muhammadiyah Gresik, 2022)
Aging is often considered as a factor in the occurrence of osteoarthritis because of weakness increased around the joints, cartilage calcification, joint flexibility and chondrocyte function decreased. Osteoarthritis can also be caused by obesity or overweight that occurs in a person with excessive or abnormal amount fat which can be detrimental to health. The aim of this study is to analyze the correlation between age also BMI and the incidence of knee osteoarthritis disease in the elderly at the outpatient unit of PKU Muhammadiyah Sekapuk Hospital.The design was used cross sectional approach, sampling using random sampling method and the number of samples as many as 31 respondents. The analysis used the Chi Square Test with a significant value of < 0.05. The results showed that p-value was 0.025 in the correlation between age and the incidence of osteoarthritis also p-value was 0.023 in the correlation between BMI and the incidence of osteoarthritis which means that there was correlation between age and body mass index and the incidence of osteoarthritis in the elderly at outpatient unit of PKU Muhammadiyah Sekapuk Hospital.